9 The 'Colchester Older Persons' Evaluation for Surgery (COPES)' Clinic: A Multidisciplinary Approach to Preoperative Management of Frail, Older Patients. (6th February 2020) - Jiang, Z; Mathew, A; Peck, L; Rudra, P; Simpson, J
Abstract: Introduction: In 2014-15, 2.5 million patients over 75 years old underwent surgery compared to 1.5 million in 2006-7. The population is aging with increasing numbers of comorbidities, and associated frailty. 1 The Royal College of Anaesthetists recommends that preoperative assessment for these complex older patients takes a "cross-specialty approach." 2 In Colchester the COPES clinic has been introduced in which selected high-risk patients are seen by a Consultant Anaesthetist and Consultant Geriatrician. This aims to medically optimise patients prior to surgery and to facilitate shared decision making. Methods: The new clinic was introduced in October 2018. The following data was collected from COPES clinic letters from October to February 2018-19 (n=46): Patient/ surgery characteristics: age, comorbidities, frailty score and any cognitive impairment Interventions: changes to medication, specialty referral, intravenous iron, diabetes optimisation, other Outcomes of surgery following the COPES clinic Patients were asked to complete feedback forms to evaluate the service. Results: 52% of patients had 4-6, and 28% had 7-9 comorbidities. The majority had Rockwood frailty scores of 4 or 5. 28% of patients had medications changed, 48% had specialty referrals, 17% received intravenous iron, 8.7% required diabetes optimisation and 28% of patients had investigations including echocardiograms, MRI and CT scans. 12/46 patients had surgery deemed unlikely to go ahead after shared decision making with patients in conjunction with the multidisciplinary team involved in their care. 2 patients died of their comorbidities after deciding not to proceed with surgery. 12/46 patients underwent surgery; 4 developed post-operative complications, none died and the mean length of stay was 3.38 days. The remaining 22/46 patients are awaiting surgery. Patient feedback questionnaires (n=10) were overwhelmingly positive. Everyone felt that they were treated with respect and that their fears were addressed and they were clear in the next steps in management. Conclusions: The introduction of the 'COPES' clinic has helped address frailty and multiple comorbidities by optimising patients' medical conditions and allowing alternatives to surgery to be considered. Patients were very satisfied with the COPES clinic and felt it has prepared them for upcoming surgery. References: 1. Lin H. Frailty and post-operative outcomes in older surgical patients: a systematic review. BMC Geriatrics, 2016. 2. RCoA. Guidelines for the Provision of Anaesthesia Services. www.pre-op.org/sites/default/files/GPAS%202016.pdf